SWARMING TERRORIST ATTACK AS AN EVOLVING THREAT FOR THE EUROPEAN SECURITY (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
This paper examines contemporary terrorism as a self-improving system that adapts to changes in the security environment. The article focuses on the study of the swarming attack as a terrorist tactic to achieve a strategic effect. The purpose of the publication is to analyse the nature of the complex coordinated terrorist attack and identify the factors that define it as an existing threat to European security. The main research methods include document study, systematic analysis and “case study”. The conclusions related to the change in the tactical methods used by terrorists will contribute to the development of adequate countermeasures by the competent authorities.